2012
DOI: 10.1111/epi.12011
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive continuous functional near‐infrared spectroscopy combined with electroencephalography recording of frontal lobe seizures

Abstract: Summary Purpose:  To investigate spatial and metabolic changes associated with frontal lobe seizures. Methods:  Functional near‐infrared spectroscopy combined with electroencephalography (EEG‐fNIRS) recordings of patients with confirmed nonlesional refractory frontal lobe epilepsy (FLE). Key Findings:  Eighteen seizures from nine patients (seven male, mean age 27 years, range 13–46 years) with drug‐refractory FLE were captured during EEG‐fNIRS recordings. All seizures were coupled with significant hemodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…Initial qualitative analysis of NIRS-data from the seizures revealed most hemodynamic changes to occur just before or in the first minutes after seizure onsets in accordance with previous NIRS studies [3,6]. We did not find any trend of changes in the pre-ictal periods, which in general exceeded the ictal-periods of the seizures.…”
Section: Resultssupporting
confidence: 90%
“…Initial qualitative analysis of NIRS-data from the seizures revealed most hemodynamic changes to occur just before or in the first minutes after seizure onsets in accordance with previous NIRS studies [3,6]. We did not find any trend of changes in the pre-ictal periods, which in general exceeded the ictal-periods of the seizures.…”
Section: Resultssupporting
confidence: 90%
“…Thus, these results indicated that hypoxia acted on the hippocampus with regional character in the SE, which was in line with hippocampal sclerosis in a postmortem study (Feast et al, 2012). Furthermore, Oxygen deprivation of the CA1, CA3 and DG of the hippocampus during epileptic seizures has been verified with MRI and EEG recording (van Eijsden et al, 2004;Nguyen et al, 2013). So studying hypoxic insults in these sub-regions may reveal the mechanism of hippocampal apoptosis in a rat model of epilepsy.…”
Section: Discussionsupporting
confidence: 53%
“…NIRS revealed significant hyperperfusion on the side of seizure foci compared with ictal single-photon-emission computed tomography in recordings of patients with nonlesional refractory frontal-lobe epilepsy. 48,49 NIRS and electroencephalography (EEG) were successfully applied simultaneously to the mouse brain to spatiotemporally track hemodynamics responses to epileptic episodes that had been induced pharmacologically. 50 Another study combining NIRS and EEG has also revealed complex local and distant oxygenation changes during temporal-lobe seizures, 51 and so this methodology can be expected to be actively used in clinical researches.…”
Section: Epilepsymentioning
confidence: 99%